Assessing plastics usage and its drivers from final demand perspectives: A case study from China. (20th November 2022) - Tan, Yiqi; Wang, Yihan; Hu, Yupeng; Wen, Zongguo; Kosajan, Vorada; Zheng, Kaixuan
Abstract: Assessing plastics using status and driving forces are vital in consumption-side governance to alleviate environmental impact aroused by extensive usage. Current researches lack to assess plastics usage embodied in upper supply chain, which would induce misunderstanding of using efficiency and sub-optimal policy design, especially in today's increasingly globalized economy. In this study, we apply Environmental Extend Input-Output Model to evaluate plastics usage from final demand perspectives, naming embodied plastics footprint. Regardless of where plastics are physically input along the supply chain, they are assigned to regional consumption account, as long as they are triggered by final demand. China is selected to conduct embodied plastics footprint evaluation, and structural decomposition analysis is combined to explore historical driving forces during the year 2002–2017. Results show plastics consumption in embodied form is too significant to ignore, with China embodied plastics import 5.3 times higher than direct plastics import. China embodied plastics footprint is 44.9 Mt in 2017 and fixed capital formation is final demand category of the largest plastics consumption (about 54% in 2017). Public and Other Services Sector (S22) is unexpectedly identified as second most high-consuming sector with its prominent plastics consumption in upper supply chain. Moreover, obvious technological flexibility of S22 is identified in historical driver analysis, in which continually upgrading production structure helps control footprint expansion triggered by the growing population and per capita consumption. A noticeable consumption pattern shifts from industrial and agricultural product-oriented to service-oriented is also found. Given the service-oriented consumption pattern expected to continue, future targeted regulation of service industry is highly recommended, especially through innovative design, supplier management and green purchasing. Highlights: Plastics consumption triggered by regional final demand, naming embodied plastics footprint is assessed in China. Technical-economic-social driving forces of China's embodied plastics footprint variation are explored over 2002–2017. Plastics consumption in embodied form is too huge to ignore. Public and other services is a hidden high-consuming sector in whole supply chain perspectives. Growing population and per capita consumption are the main drivers of China embodied plastics footprint.